Understanding and Attitudes of Religious Moderation among Teachers in Al-Qur'an Education Centers - Fadillah, Galih Fajar; Al Fatah, Husin; Mashar, Aly (Al-Adyan: Journal of Religious Studies, 2024)
This qualitative study examines the understanding and attitudes of TPQ (Taman Pendidikan al-Qur'an) teachers in Sawit District, Boyolali, Indonesia towards religious moderation and the factors influencing these attitudes. The research used a qualitative approach through in-depth interviews, observations, and document analysis to explore the lived experiences and perspectives of these teachers. The study emphasizes the significance of religious moderation such as tawasuth (moderation), national commitment, tolerance, cultural accommodation, and anti-violence in fostering societal harmony. It highlights key challenges, opportunities, and supports within the moderation learning process. This research is distinctive in its focus on TPQ teachers, a critical yet underexplored group in religious education. The findings underscore the need for enhanced educational initiatives, promotion of moderation values, and empowerment of influential societal figures to cultivate stronger attitudes of religious moderation. By addressing regional and educational contexts, the study offers new insights into grassroots-level efforts to promote religious moderation.Studi kualitatif ini meneliti pemahaman dan sikap guru TPQ (Taman Pendidikan al-Qur'an) di Kecamatan Sawit Boyolali, Indonesia terhadap moderasi beragama dan faktor-faktor yang memengaruhi sikap tersebut. Penelitian menggunakan pendekatan kualitatif melalui wawancara mendalam, observasi, dan analisis dokumen untuk mengeksplorasi pengalaman dan perspektif hidup para guru tersebut. Studi ini menekankan pentingnya moderasi beragama seperti tawasuth (moderasi), komitmen nasional, toleransi, akomodasi budaya, dan antikekerasan dalam membina kerukunan masyarakat. Studi ini menyoroti tantangan, peluang, dan dukungan utama dalam proses pembelajaran moderasi. Penelitian menjadi unik karena berfokus pada guru TPQ, kelompok yang kritis namun kurang dieksplorasi dalam pendidikan agama. Temuan penelitian menggarisbawahi perlunya peningkatan inisiatif pendidikan, promosi nilai-nilai moderasi, dan pemberdayaan tokoh masyarakat yang berpengaruh untuk menumbuhkan sikap moderasi agama yang lebih kuat. Dengan membahas konteks regional dan pendidikan, penelitian ini menawarkan wawasan baru tentang upaya masyarakat akar rumput untuk mempromosikan moderasi agama.